Molecular Monitoring in Adult Philadelphia Chromosome-Positive Acute Lymphoblastic Leukemia with the Variant e13a3 BCR-ABL1 Fusion. (27th June 2019) - Crampe, Mireille; Kearney, Laura; O'Brien, David; Bacon, C. Larry; O'Shea, Derville; Langabeer, Stephen E.
Abstract : Monitoring BCR-ABL1 transcript levels in patients with Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph+ ALL) is a widely adopted method to assess response to therapy. However, a small minority of Ph+ ALL patients express variant BCR-ABL1 transcript types, usually due to splicing of alternative BCR or ABL1 exons. Whether patients expressing these rare, variant BCR-ABL1 transcripts have a distinct phenotype or response to therapy is not known due to the limited number of reported cases. Here, we report the presenting features of Ph+ ALL in a young adult with a variant e13a3 BCR-ABL1 fusion. Molecular monitoring reflected the disease response from diagnosis through allogeneic stem cell transplantation which resulted in undetectable e13a3 BCR-ABL1 transcripts. This case highlights the value of molecular monitoring in Ph+ ALL patients with variant BCR-ABL1 transcripts and the requirement for standardization of such assays.